Implant removal rate after partial carpal arthrodesis in dogs: A retrospective analysis of 22 cases - Choi, Caroline J.; Balara, Jason M.; Casale, Sue A.; Wendelburg, Kirk L. (Frontiers in Veterinary Science, 2023)
The purpose of this study is to determine the rate of implant removal after partial carpal arthrodesis and to investigate factors associated with implant removal. Case records of 22 dogs that underwent partial carpal arthrodesis at two private veterinary referral hospitals were reviewed. Details retrieved were body weight at time of surgery, sex, neuter status, breed, age, cause of carpal hyperextension injury, joint(s) involved in carpal hyperextension injury, laterality, type of implant, administration of post-operative antibiotics, post-operative outcome and indication for implant removal. Association between these factors and implant removal was evaluated. Of 22 partial carpal arthrodesis, 12 (55%) had implant removal due to persistent lameness and 9/12 (75%) returned to full and acceptable function after implant removal. Indications for implant removal were implant interference (8), infection (4), and migration (1). When comparing type of implant, there was a significant difference when observing implant removal rates (p = 0.04). All 5 dogs with pins and wires (100%) required implant removal. Of 17 dogs with a plate, 7 (41.2%) required implant removal. Implant removal was performed on average 114 days post-operative. Implant removal after partial carpal arthrodesis was frequent and was commonly indicated due to pin and wire fixation or plate implant interference. This study may impact how we prepare clients for potential post-operative complications and implant removal when recommending partial carpal arthrodesis.